EFFECT OF COUNSELOR COMPETENCE ON STUDENT INTEREST IN GROUP GUIDANCE SERVICES - SITI ZAHRA BULANTIKA (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2019)
Personality counselor competence in the implementation of guidance and counseling, one of them in group guidance services are needed to be a competent counselor. It will continue to increase, in line with the development of counseling, especially to foster enthusiasm and be one of the reasons that students have an interest in participating in group counseling services. Attention plays a significant role in the lives of students and has a tremendous impact on attitudes and behavior. Through the provision of group guidance services, students are directed to participate in group discussion activities and function to prioritize the development of communication and socialization skills.